2015
DOI: 10.1111/epi.13284
|View full text |Cite
|
Sign up to set email alerts
|

Laser interstitial thermal therapy for medically intractable mesial temporal lobe epilepsy

Abstract: SUMMARYObjective: To describe mesial temporal lobe ablated volumes, verbal memory, and surgical outcomes in patients with medically intractable mesial temporal lobe epilepsy (mTLE) treated with magnetic resonance imaging (MRI)-guided stereotactic laser interstitial thermal therapy (LiTT). Methods: We prospectively tracked seizure outcome in 20 patients at Thomas Jefferson University Hospital with drug-resistant mTLE who underwent MRI-guided LiTT from December 2011 to December 2014. Surgical outcome was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
290
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 314 publications
(307 citation statements)
references
References 43 publications
13
290
2
2
Order By: Relevance
“…Patients with MTS had slightly higher rates of seizure freedom than patients without MTS (61% vs 53%) at 6 months, but this was not a statistically significant difference. At Thomas Jefferson University Hospital, we observed that about 40% of the 20 patients who underwent LiTT for MTLE were free of disabling seizures at 2 years [7]. The number of patients as too small for us to compare outcome between patients with and without MTS, but only 1 of the 3 patients without MTS was seizure-free after LiTT.…”
Section: Mtlementioning
confidence: 93%
See 3 more Smart Citations
“…Patients with MTS had slightly higher rates of seizure freedom than patients without MTS (61% vs 53%) at 6 months, but this was not a statistically significant difference. At Thomas Jefferson University Hospital, we observed that about 40% of the 20 patients who underwent LiTT for MTLE were free of disabling seizures at 2 years [7]. The number of patients as too small for us to compare outcome between patients with and without MTS, but only 1 of the 3 patients without MTS was seizure-free after LiTT.…”
Section: Mtlementioning
confidence: 93%
“…A disposable cooling catheter cools the laser fiber and surrounding tissues to minimize carbonization [6]. Most epilepsy centers set the target cytotoxic temperature between 60°C and 80°C and multiple ablations (2-3) are performed for selective laser amygdalohippocampectomy [7]. The thermal image is used to approximate the volume ablated or Bdamage zone^ [8].…”
Section: Principals Of Littmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Our own institutional experience has demonstrated similar results, with 53% seizure freedom at 6 months, 36.4% at 1 year, and 60% at 2-year follow-up (loss to follow-up in a small patient sample resulting in the variable results within the study period). 18 Results 17 Intra-operatively, a manual arc-ring system is used with the CRW frame to guide placement of the anchor bolt, instead of the robotic system, given the time involved setting up the robot is not justified for a single trajectory. After drilling placement of a bone anchor bolt, a laser probe is advanced to target.…”
Section: Responsive Neurostimulationmentioning
confidence: 99%